Advances in the development of antiviral compounds for rotavirus infections - Tohmé Chapini, María Julieta (2021)
Group A rotaviruses (RVAs) are the major cause of severe acute gastro-enteritis (AGE) in children under 5 years of age, annually resulting in nearly 130,000 deaths worldwide. Social conditions in developing countries that contribute to decreased oral rehydration and vaccine efficacy and the lack of approved antiviral drugs position RVA as a global health concern. In this minireview, we present an update in the field of antiviral compounds, mainly in relation to the latest findings in RVA virion structure and the viral replication cycle. In turn, we attempt to provide a perspective on the possible treatments for RVA-associated AGE, with special focus on novel approaches, such as those representing broad-spectrum therapeutic options. In this context, the modulation of host factors, lipid droplets, and the viral polymerase, which is highly conserved among AGE-causing viruses, are analyzed as possible drug targets.